EU S TRANS EUROPEAN NETWORK FROM THE POINT OF LOGISTICS POTENTIAL OF TURKEY (Third Sector Social Economic Review, 2015)
One of the important subjects of Turkey’s adoptation to the EU is EU’s Trans-Europan Networks. These Networks; namely transport, energy and telecommunication. Trans European Transport Network, is the great opportunitiy for Turkey to reach biggest market, namely Western Europe. For this reason in this report, primarily Trans European Network concept of EU and the future of this politicy is considered, and adoptation situation of Turkey is evaluated from the lojistic perspective. Screening method has been used and some proposals have been done for the future. Subject is very important for the Turkey’s future. Turkey has to prepare with overall concept for the adoptation on this issue.
Keywords: EU; Logistics; TEN-T; Trans European Network; adoptation